Galactosialidosis in two siblings - Yüce, Aysel; Koçak, Nurten; Besley, Guy T. (The Turkish Journal of Pediatrics, 1996)
Galactosialidosis is a rare lysosomal storage disease associated with deficiencies of α-galactosidase and β-neurominidase. In this report, two siblings with galactosialidosis, resembling Niemann-Pick disease with the presence of foamy cells in multiple organs, splenomegaly and prominent hepatomegaly, are presented. Galactosidase deficiency and an increased number of urinary sialic acid compounds were determined in these cases, and prenatal diagnosis was performed for their fourth sibling. Besides the presence of the typical clinical features, enzyme study is essential for the diagnosis of lysosomal storage disease and it facilitates in making the prenatal diagnosis.